FAKTOR-FAKTOR YANG MEMENGARUHI MORAL DISENGAGEMENT MAHASISWA PPKN FKIP UNIVERSITAS LAMPUNG - Devi, Sandriana; Muhammad Mona Adha; Devi Sutrisno Putri; Berchah Pitoewas; Rohman (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the factors influencing moral disengagement among PPKn students at the University of Lampung. The factors examined include external and internal factors that contribute to students' tendency to release moral control. This study used a quantitative approach with a survey method of 66 PPKn students at the University of Lampung. Data analysis was conducted using descriptive techniques through frequency distribution to determine the tendency of moral disengagement levels for each indicator. The results indicate that PPKn students at the University of Lampung are in the dominant category of moral disengagement, with the most dominant mechanisms being shifting of responsibility. Students tend to release personal moral responsibility on the grounds of actions carried out collectively, based on orders, or due to group pressure and academic demands. Other mechanisms such as moral justification, favorable comparisons, and distortion of consequences also strengthen students' tendency to justify unethical behavior.